Personal health care in the conditions of systemic changes in society - Borysiuk, Alla; Rodchenkova, Iryna; Zavatskа, Natalia; Zavatskуі, Yuri; Shapovalova, Valentine (Теоретичні і прикладні проблеми психології, 2023)
The article describes the means of personal health protection in the conditions of systemic changes in society. The process of forming health-preserving behavior includes assessment and self-assessment of the individual's health. Projects to support the state of health of the individual, aimed at prolonging the active creative period of life, should have a systemic nature. This involves not only the formation of appropriate social programs, the creation of appropriate conditions for the external environment and infrastructure (including information), but also the introduction of health-preserving technologies into the activities of economic organizations, increasing the importance of environmental culture, physical culture and sports in the educational, industrial, and everyday life of the population taking into account the complexity, integrated qualified influence of various subjects of socialization (sociologists, teachers, medical workers, psychologists, parents, managers of enterprises, institutions, power and administrative structures and the population in general). Key words: personality, health care, systemic changes in society.